Embedded mistrust then and now: findings of a focus group study on African American perspectives on breast cancer and its treatment. Issue 4 (7th August 2016) - Ferrera, Maria J.; Feinstein, Rebecca T.; Walker, William J.; Gehlert, Sarah J.
Abstract: The risk of African American women dying from breast cancer is estimated to be 41% higher than that of White women throughout the USA. Using a community-based participatory research (CBPR) perspective, this qualitative study elicited attitudes, beliefs and concerns about breast cancer and its treatment amongst African Americans living in Chicago. Five hundred and three women and men were recruited from 15 of Chicago's predominantly African American South Side neighborhoods. Participants were interviewed in 49 focus groups, 2–3 focus groups representing each neighborhood. Grounded theory was used to analyze data. A prevalent theme in the analysis was a general sense of mistrust amongst African Americans towards breast cancer treatment and the health care system at large. This theme involved notions of being treated like a guinea pig; living in the legacy of Tuskegee and other forms of historically rooted experimentation on African Americans; and being maltreated because of race. These findings suggest that historical and contemporary incidents remain a point of debate. Findings warrant the promotion of increased cultural sensitivity amongst health professionals regarding this historically rooted mistrust and its present-day implications.